Revisiting the addition reaction of TeCl4 to alkynes: the crystal structure and docking studies of 1-chloro-2-trichlorotelluro-3-phenyl-propen-2-ol - Cunha, Rodrigo L. O. R.; Zukerman-Schpector, Julio; Caracelli, I.; Comasseto, Joao V. (Elsevier B.V., 2006)
Tellurium tetrachloride adds to alkynes via two pathways: a concerted syn addition, that yields Z-tri- and tetra-substituted alkenes or by an anti addition that yields E-alkenes. The mechanistic aspects of these divergent pathways have been reevaluated at the light of crystallographic data. The molecules, of the title compound, in the crystal, are associated in a helical fashion with a Te...Te pitch of 6.3492(6) angstrom. As it exhibits inhibitory activity for cathepsin B and in order to gain more insight of the inhibition mechanism, a docking study was undertaken providing insight on why organic telluranes are more efficient inhibitors than inorganic ones as AS-101. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: tellurium tetrachloride; electrophilic addition; docking; cathepsin B; supramolecular self-assembly